The Lexicalization Across Languages (a Cultural Relativity in Mongondownese Students) - Andiani Rezkita Nabu (English Language in Focus (ELIF), 2023)
This study focused on identifying the types of lexicalization across languages occured in Mongondownese English language learners’ oral form, and finding out some factors contributed their lexicalization. In this study, it was analyzed by using the canonical theory by Kadarisman (2009) about types of lexicalization across languages, which is synthesized by using pre survey/field orientation, interview, and recording audio and audio-visual material as technique of data collecting. Therefore, by involving 8 Mongondownese students of English department as the participants, finally the researcher concluded that there are three kinds of across languages lexicalization occur in participants utterance namely, equal lexicalization, unequal (culture-specific) lexicalization, and unbalanced lexicalization. Furthermore, these are caused by the cultural factor and the limitedness of individual ability factor.